Effect of farm yard manure and planting densities on growth, yield and quality of okra under natural farming - Alam, Shariq Mahmood; Syed Ishtiaq Haider, Muhammad Arshad Ullah; Syeda Sana Aamir, Nausherwan N. Nawab; Mahmood, Imdad Ali (Horticultural Biotechnology Research, 2019)
A field study was conducted to investigate the effect of farm yard manure and planting densities (P x P 10, 15, 20 and 25 cm and R x R 60 cm) under natural farming condition at National Agricultural Research Centre, Islamabad during 2016. The land was incorporated with well rotten farm yard manure (FYM) @ 25 t ha-1 in respective plots (4 x 8 meter) one week before bed preparation and mixed thoroughly in the soil. Seeds of okra (Abelmoschus esculentus L., var. Pusa Green) were sown according to the plan following split plot design with four replications. The crop was allowed to stand till maturity and data on growth traits were recorded. Among plant densities, 10 and 15 cm P x P and FYM incorporation @ 25 t ha-1 produced comparable fresh pod yield (11.22 and 10.97 t ha-1, respectively) which was 25 and 24 % higher than that of without FYM application. Dense populated crop i.e., 10 and 15 cm P x P performed better than rest of planting densities through improved fresh pod yield with comparatively improved quality. Dense populated treatment (P x P 10 cm) and FYM application @ 25 t ha-1 produced better quality fruits with less crude fiber content (9.89 %) and higher moisture content (79.14%) as compared to without FYM application (10.93 and 77.49 %) respectively that indicates more accumulation of dry matter content in fruits.